Trams, Trials and Tribulations: the development of Cathedral Square, Christchurch 1900-18 - May, Jenny; Ross, Amanda (Architectural History Aotearoa, 2004)
Cathedral Square Christchurch is the city's premier urban space. Yet it is without doubt the most debated and controversial two and half hectares of urban design space in the city. Set out in the shape of cross rather than a square, the last five decades of the nineteenth century saw just as much controversy over its design and use as did the entire twentieth century and on into the beginnings of the twenty-first century. Over this time its design has been the butt of jokes, the subject of constant political debate and subject of many learned articles, seminars and conference papers. The period 1900 to 1918 was one of intensive design change as Christchurch moved into the era of electric trams, motor buses and motor cars. While handsome buildings grew on the square's perimeter during this period, in 1907 a less than attractive architecturally-designed transport shelter appeared in its centre causing architect Samuel Hurst Seager, a member of the Christchurch Beautifying Society, to describe it as a public building of "… appalling ugliness." Inspired by the title "Tramway Trials and Tribulations - the saga of the tramway shelter" this paper will examine the design issues surrounding Cathedral Square during the period 1900-1918 – a period that saw the first competition to improve the aesthetic reading of this space.